Composition of the essential Oil of Teucrium chamaedrys L. (Lamiaceae) from Turkey - Bagci, Eyup; Yazgin, Ayse; Hayta, Sukru; Cakilcioglu, Ugur (Academic Journals, 2010)
The essential oil obtained by hydrodistillation from Teucrium chamaedrys L. (Lamiaceae) from Turkey was analyzed by (GC) and (GC/MS). Thirty six components in aerial parts of T. chamaedrys were identified representing (90.8%) of the oils. Main constituents of the oil were found as germacrene D (32.1%), beta-caryophyllene (14.2%), delta.-cadinene (13.1%), bicyclogermacrene (6.7%) and beta-farnesene (4.3%). The results were discussed with the genus pattern in means of medicinal purpose and natural products.
Keywords: Teucrium chamaedrys; germacrene D; Lamiaceae; essential oil; Turkey